2020
DOI: 10.1523/jneurosci.2139-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enhancement of Object Representations through Multisensory Integration

Abstract: Objects are the fundamental building blocks of how we create a representation of the external world. One major distinction among objects is between those that are animate versus those that are inanimate. In addition, many objects are specified by more than a single sense, yet the nature by which multisensory objects are represented by the brain remains poorly understood. Using representational similarity analysis of male and female human EEG signals, we show enhanced encoding of audiovisual objects when compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Compared to semantically incongruent or meaningless (arbitrary) multisensory stimuli, semantically congruent stimuli are more easily identified and remembered (e.g. Laurienti et al 2004;Murray et al, 2004;Doehrmann & Naumer 2008;Chen & Spence, 2010;Matusz et al, 2015a;Tovar et al 2020;reviewed in ten Oever et al 2016;Murray et al, 2016b;Matusz et al 2020) and also, more strongly attended (Matusz et al 2015b(Matusz et al , 2019a(Matusz et al , 2019breviewed in Soto-Faraco et al, 2019;Matusz et al 2019c). For example, Iordanenscu et al (2009) demonstrated that search for naturalistic objects is faster when accompanied by irrelevant albeit congruent sounds.…”
Section: Top-down Contextual Factors In Attentional Controlmentioning
confidence: 99%
“…Compared to semantically incongruent or meaningless (arbitrary) multisensory stimuli, semantically congruent stimuli are more easily identified and remembered (e.g. Laurienti et al 2004;Murray et al, 2004;Doehrmann & Naumer 2008;Chen & Spence, 2010;Matusz et al, 2015a;Tovar et al 2020;reviewed in ten Oever et al 2016;Murray et al, 2016b;Matusz et al 2020) and also, more strongly attended (Matusz et al 2015b(Matusz et al , 2019a(Matusz et al , 2019breviewed in Soto-Faraco et al, 2019;Matusz et al 2019c). For example, Iordanenscu et al (2009) demonstrated that search for naturalistic objects is faster when accompanied by irrelevant albeit congruent sounds.…”
Section: Top-down Contextual Factors In Attentional Controlmentioning
confidence: 99%
“…Many paradigms probe multisensory binding using paradigms involving one stimulus per modality. Whether and how results obtained using these generalize to real-life multisensory object perception remains unclear (Badde et al, 2023;Bizley, Maddox, & Lee, 2016;Duarte et al, 2023;Kirsch & Kunde, 2023;Newell et al, 2023;Tovar et al, 2020). In a step towards this direction, we asked how the presence of two visual stimuli shapes multisensory perception in the audio-visual spatial ventriloquism paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that the relative contribution of individual stimuli in real‐life will depend on additional factors beyond their spatio‐temporal alignment. It is known that the relative weight among two stimuli is shaped by task‐relevance, semantic congruency, prior expectations and attention (Bizley, Jones, & Town, 2016; Delong & Noppeney, 2021; Noppeney, 2021; Talsma et al, 2010; Tovar et al, 2020; Zuanazzi & Noppeney, 2020). In particular, the role of attention is difficult to dissociate from other aspects of multisensory computation, as attention may be assigned unconsciously and automatically based on multiple attributes, including the timing of individual stimuli (Donohue et al, 2015; Talsma et al, 2010; van der Burg et al, 2008b; Zhaoping, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Just as these processes evolve extremely rapidly, decision making also can evolve rapidly and below the level of conscious awareness (Figure 1). For example, during a go/no-go task, neural activity and behavioral measures were evident at intervals of 100 to 200 ms. and 350 to 500 ms. after stimulus presentation, corresponding to the time points of sensory evidence accumulation and decision making (Tovar et al, 2020).…”
Section: Neural Processes Of Believingmentioning
confidence: 99%